Research on a novel modifying furnace for converting hot slag directly into glass-ceramics. (20th January 2018) - Dai, Wenbin; Li, Yu; Cang, Daqiang; Lu, Xiang; Zhao, Guizhou; Guo, Junxiang
Abstract: Utilization of hot slag and its waste heat (1450–1650 °C) constitute a great challenge for iron and steel industry. In recent years, a method different from the traditional one, has been developed to integrate utilization of waste heat and mass of hot slag, which has as an objective to prepare value-added materials and to establish a much cleaner production. During the process, composition and structure of hot slag are modified to meet the need of target materials, while its waste energy is utilized to lower heat consumption during the melting and reactions of raw materials. To carry out such modification process, a novel modifying furnace, which was composed of an upper part, cyclone furnace (CFu) and the bottom part, modifying chamber (MCh), was designed and constructed during this research. Experiments to investigate the effect of different process parameters on temperature distribution in the furnace and preparation of glass-ceramics from the modified hot slag were conducted. Cooled modifiers mainly composed of fly ash were initially heated in CFu and then placed into the molten bath in MCh to mix with hot steelmaking slag. During the modification process, the maximum temperature reached 1500 °C in the mid-bottom part of CFu. An increase of a secondary air stream could decrease the CFu temperature but had no significant impact on the MCh temperature. Input of a primary oxygen-rich air stream could guarantee higher temperature in both the CFu at 1400–1600 °C and the MCh at 1400–1450 °C. The optimum parameter of velocities was (100–120) × 2 m 3 /h for primary air stream, (10–16) × 2 m 3 /h for oxygen gas stream and 315–568 m 3 /h for secondary air stream. To achieve efficient flow ability and take advantage of more hot slag, the steel slag was modified to include a higher basicity (CaO/SiO2 ) of 0.6–0.7 compared to the traditional product (commonly below 0.5). Glass-ceramics, derived from the water quenched modified slag after heat treatment, was finally prepared with excellent performances. Highlights: Hot steel slag was utilized together with its waste heat. A modifying furnace was designed for hot slag modification. Hot modification process was controlled by temperature distribution adjustment. Glass-ceramics derived from modified slags were obtained with excellent properties.